Implementasi Fungsi Pengayoman Kepolisian Terhadap Penyelesaian Perkara Tindak Pidana Persetubuhan Anak Pada Suku Pamona Kabupaten Luwu Timur (PETITUM, 2025)
This empirical legal research aims to analyze the implementation, obstacles, and solutions regarding the police's protective function in resolving child sexual intercourse cases within the Pamona Tribe, East Luwu Regency. The findings indicate that the implementation of the police's protective function must be carried out comprehensively, empathetically, and professionally, prioritizing the child's best interests as the primary focus. In fulfilling their role as community protectors, the police encounter significant obstacles, including low reporting rates, lack of specialized investigator competency, difficulties in gathering evidence, social and environmental intervention, the victim's psychological trauma, inadequate supporting facilities, and prevailing social stigma or discrimination. Strengthening institutional capacity and community collaboration is essential to optimize the protective function in resolving such legal cases.